14th International Symposium on Thrombolysis, Thrombectomy and Acute Stroke Therapy: Proceedings and summary of discussions. Issue 4 (June 2019) - Sheth, Sunil A; Lopez-Rivera, Victor; Lee, Songmi; Savitz, Sean I; Liebeskind, David S; Grotta, James C; ,
The 14th International Symposium on Thrombolysis, Thrombectomy and Acute Stroke Therapy (TTST) took place in Houston, Texas on 21–22 October 2018. Attended by 150+ invited global experts, the objectives of TTST 2018 were to explore the changing landscape of acute ischemic stroke therapy and to address current controversies in thrombolysis and thrombectomy, including expanding access and systems of care with global relevance. This article summarizes the proceedings of TTST 2018. The key points of each session are listed below, the full text of presentations and discussion are available in the online supplement, and the full list of contributing authors appear in the Appendix at the end of this article.